DNA or protein? Capillary zone electrophoresis–mass spectrometry rapidly elucidates metallodrug binding selectivity. Issue 57 (4th July 2017) - Artner, Christian; Holtkamp, Hannah U.; Kandioller, Wolfgang; Hartinger, Christian G.; Meier-Menches, Samuel M.; Keppler, Bernhard K.
Abstract : A novel capillary zone electrophoresis–mass spectrometry (CZE–MS) approach allows the characterization and quantification of the binding preferences of metal-based anticancer agents to biomolecules. Abstract : A novel capillary zone electrophoresis–mass spectrometry (CZE–MS) approach allows the simultaneous characterization and quantification of the binding of metal-based anticancer agents to biomolecules. Moreover, for the first time, oligonucleotide metallation was resolved at single-nucleotide resolution by MS.